THE INFLUENCE OF REPUTATION, SERVICE QUALITY, AND TRUST ON CONSUMER DECISIONS IN USING BLUEBIRD SERVICES AT SHIA - Tambunan, Riama Juliana; Hamad, Ibnu; Santoso, Prasetya Yoga (Universitas prof. Dr. Moestopo (Beragama), 2025)
The objective of this research is to analyze the influence of reputation, service quality and trust on consumer decisions in using PT transportation services. Blue Bird at Soekarno-Hatta Airport. The research was conducted quantitatively with an explanatory research design and a sample size of 100 respondents. The sample population includes various demographic groups with a minimum age of 20 years, male and female with various educational backgrounds, and used Blue Bird transportation services either regularly or occasionally in the last 6 months. The data collection technique in this research was a structured questionnaire and sampling used non-probability sampling with the snowball technique. Statistical analysis and data processing were conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach, utilizing the PLS-SEM version 4.0 software. The research results show that: (1) Reputation has a positive and significant effect on consumer decisions, (2) Service quality has a positive and significant effect on consumer decisions, (3) Trust has a positive and significant effect on consumer decisions (4) Trust is the dominant factor that influences consumer decisions.